Relationship between bank value, tax avoidance, and profitability - Mohammad Fawzi Shubita (Banks and Bank Systems, 2024)
This study explores the intricate relationships between bank value, tax avoidance, and profitability, which significantly affect the stability and strategies of financial institutions worldwide. Understanding these connections is vital for comprehending the financial dynamics of banks, key players in economic growth and stability. The study focuses on these three factors due to their intertwined roles in shaping fiscal policy effectiveness, shareholder satisfaction, and overall financial health. The aim of this study is to explore the relationships between the bank value, tax avoidance and profitability aiming to clarify their interactions and their impact on the Jrdanian banks. Ordinary Least Squares regression analysis is employed using a mixed-methods approach, including quantitative regression analysis and qualitative assessments. The study results reveal a significant direct link between bank tax avoidance and profitability. The increase in Return on Assets is associated with a substantial increase in tax avoidance. In the expanded model, bank value and size did not exhibit statistically significant incremental information over profitability in explaining tax avoidance. Profitability emerges as a dominant factor, overshadowing the potential impact of size and value. The results underscore profitability as a key driver in bank tax strategies, highlighting a potential area for regulatory scrutiny and strategic realignment. In conclusion, the study underscores the pivotal influence of bank profitability on tax avoidance strategies. Policymakers, practitioners, and researchers are encouraged to recognize the prominence of profitability in formulating tax strategies.